Clinical Analysis of 42 Cases of Ocular Ischemic Syndrome. (11th March 2018) - Luo, Jingyi; Yan, Zhichao; Jia, Yu; Luo, Rongjiang
Abstract : Ocular ischemic syndrome (OIS) is a severe ocular disease caused by ocular hypoperfusion due to stenosis or occlusion of the common or internal carotid arteries. OIS is easily misdiagnosed or undiagnosed given its asymptomatic onset and complicated ocular manifestations. The present study reviewed 42 patients with OIS, including 30 males (71.43%), 29 older patients (69.05%, >61 yrs), and 35 patients (83.33%) with two or more systemic diseases. Only 6 patients had ocular symptoms as the initial signs upon visiting the Department of Ophthalmology of three hospitals (the First Affiliated Hospital, Sun Yat-sen University; Zhongshan Ophthalmic Center, Sun Yat-sen University; and the Second Affiliated Hospital, Guangzhou Medical University). The ocular symptoms varied from visual deterioration to periorbital pain. Thirty-seven patients (88.10%) complained of constitutional symptoms. Ocular manifestations were diverse and involved both anterior and posterior segments. We reported a case of corneal edema and corneal epithelium erosion in the ipsilateral eye due to internal carotid artery stenosis. As the clinical manifestations of OIS are complex, ophthalmologists must carefully examine patients to avoid a misdiagnosis or a failure to diagnose. The management of OIS requires cooperation with cardiologists and neurologists.